2013
DOI: 10.3892/ol.2013.1162
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid supplementation does not affect N-methyl-N-nitrosourea-induced renal preneoplastic lesions in young Lewis rats

Abstract: Arachidonic acid (AA) is naturally found in human breast milk. AA, together with docosahexaenoic acid, is commonly added as a functional food ingredient to commercial infant formula worldwide, in accordance with the international standards of Codex Alimentarius. However, few studies of the possible renal carcinogenic effects of AA supplementation during neonatal life have been performed. The effect of dietary AA supplementation in dams during gestation and lactation was investigated on N-methyl-N-nitrosourea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…These results agree with those of our previous study [ 16 ]. Yoshizawa et al reported that an ARA-rich diet for dams during gestation and lactation does not modify N -methyl- N -nitrosourea-induced renal preneoplastic lesions in their offspring [ 25 ], indicating that exogenous free-form ARA does not induce inflammation or oxidative stress in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those of our previous study [ 16 ]. Yoshizawa et al reported that an ARA-rich diet for dams during gestation and lactation does not modify N -methyl- N -nitrosourea-induced renal preneoplastic lesions in their offspring [ 25 ], indicating that exogenous free-form ARA does not induce inflammation or oxidative stress in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen surviving female rats were used for the analysis at the age of 16 weeks. Rats were maintained under specific pathogen-free conditions and had free access to water and a CE-2 diet (CLEA Japan, Tokyo, Japan) according to a previous study 12 . Animals were housed in plastic cages with paper-chip bedding (Paper Clean, SLC, Hamamatsu, Japan) in an air-conditioned room at 22 ± 2°C and 60 ± 10% relative humidity with a 12-hr light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrosourea compounds including N -methyl- N -nitrosourea (MNU) also possess carcinogenic potency in the kidneys 8 , 9 , and MNU induces renal mesenchymal tumors (RMTs) and nephroblastomas in rats 10 , 11 , 12 . The formation and persistence of DNA adducts, such as O 6 -methylguanine, and K- ras codon 12 and 16 point mutations in renal cortical tubular cells and/or mesenchymal interstitial cells is related to the tumor development induced by alkylating agents 9 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies, the AA-supplemented diet was formulated by CLEA Japan, Inc. (Tokyo, Japan) (9,10,31). AA was purchased from Cargill Alking Bioengineering LLC (Wuhan and Hubei, China).…”
Section: Methodsmentioning
confidence: 99%